How to Write Your Undergraduate Dissertation - Greetham, Bryan (New York Palgrave Macmillan, 2009)
Examining each essential stage of research and writing a dissertation, this book teaches students across all disciplines how to generate ideas and develop them into original research projects. It clearly explains the best way of planning and conducting research using qualitative and quantitative techniques and primary and secondary material; enabling the student to successfully plan and write a clear and concise dissertation.